Electricity cost optimization in a renewable energy - Pereira, Sérgio (2013)
The variable electricity output of the renewable energy sources (RES) power plants, such as wind and hydro power technologies, is seen as an important challenge for the electricity system managers. This paper addresses the problem of an electricity system supported mainly on hydro, thermal and wind power plants, presenting a short-term model planning. A binary mixed integer non-linear optimization model for one year planning with hourly time step is described and applied to a system close to the expected Portuguese electricity scenario for the year 2020. The main objective of this paper was to analyze the impact that different levels of installed wind power and hydropower have in the operation of thermal power units. Besides that, the analysis of results demonstrate the influence that the characteristics of the seasons of the year has on the renewable power units electricity generation and by this way on the total production cost of the system.